How learning theories can be applied in accounting education - Silva, Ilídio (2018)
Introduction: Having expertise in accounting is not enough to be an effective accounting educator. Knowledge about learning theories, learning styles, different types of assessment, and the variety of available teaching methods, is also fundamental to be a good accounting educator. Objectives: Analyse which learning theories can be applied in accounting education and how they can help accounting educators to improve the learning process according with their competences. Methods: Literature review about the professional accountant competencies and analysis of the learning theories application in accounting education. Results: Based on certain learning theories (behaviourism, humanism, cognitivism, social cognitivism, and constructivism), provide a set of recommendations to accounting educators in order to improve the learning process. Conclusions: Even if an educator has a very good academic background, and significant professional experience in the teaching area; even if he uses innovative teaching technologies, if the educator does not listen learners; if the educator does not understand that each individual learner has a different background, cultural experience and way of learning; if the educator does not understand that there is no standardized way to teach, this educator will not succeed.